Diet-driven microbiome changes and physical activity in cancer patients - Ciernikova, Sona; Sevcikova, Aneta; Stevurkova, Viola; Mego, Michal (Frontiers in Nutrition, 2023)
Exploring the role of the gut microbiome in oncology is gaining more attention, mainly due to its ability to shape the immune system in cancer patients. A well-balanced microbial composition forms a symbiotic relationship with the host organism. Mounting evidence supports the potential of modifiable lifestyle factors, such as diet and physical activity, in restoring intestinal dysbiosis related to cancer development and treatment. In this Minireview, we describe the host-microbiome interplay following different dietary patterns, including a high-fat diet, fiber-rich diet, diet rich in rice and beans, Mediterranean diet, ketogenic diet, and physical activity in preclinical findings and clinical settings. According to the results, nutrition is a critical factor influencing the composition of gut microbial communities. Therefore, knowledge about the patient's nutritional status in pre-treatment and treatment becomes crucial for further management. A combination of individualized dietary habits and professional training plans might help to maintain gut homeostasis, potentially improving the response to anti-cancer therapy and the quality of life in cancer survivors. However, a deep understanding of underlying mechanisms and large clinical trials are needed to uncover clinically relevant correlations for personalized treatment approaches leading to better outcomes for cancer patients.